A Q methodology study to investigate the experiences of head and neck cancer patients from diagnosis to 1 year. (4th May 2017) - Reid, K. J.; Swift, A.; Mehanna, H.
Abstract : The experiences of disease and treatment for patients diagnosed with head and neck cancer (H&NC) are known to be important indicators of the quality of care but are represented poorly in the literature. Survival is a major outcome measure to which health‐related quality of life (HRQoL) adds detail but outcomes are not fully representative of the patients' experiences because quality of care and reality of treatment are overlooked. This study explored the HRQoL, quality of care and reality of treatment themes using a mixed‐methods approach, Q Methodology. In total, 18 participants who were at least 12 months post‐diagnosis rank‐ordered 45 prepared statements to reflect their own experiences of H&NC. After the statements had been sorted, the participants reviewed the order in an interview to clarify experiences. The statements become a way of facilitating the discussion because the participant can explain the position of specific statements that are notable for them. The ranking was factor‐analysed case‐wise and five factors provided the best conceptual fit: meaning and attachment to illness; overwhelmed by the cancer; surviving or not; change and recovery; and keep control for the greater good of others. The findings suggest there are distinct ways that H&NC patients experience the disease and its treatment. The concept of the experience being different and defined for individuals has practical implications at a clinical level and is a way of ensuring care is truly patient‐centred.